(untitled) (Analysis in Theory and Applications, 2025)
The main purpose of this paper is to establish the distributional boundary values of functions in the weighted Hardy space, which improves the results of Carmichael in [4] and [8], where the weight function is linear. As our main result, we will prove that f(z) in H(ψ, Γ) has the Z' boundary value and can be expressed by the inverse Fourier transform of a distribution. Next, we will establish the S' boundary value under stronger assumptions and give more precise expression if f(z) also converges to U ∈ D'_L^p(R^n), where 1 ≤ p ≤ 2. In addition, we will also study the inverse result, in which we will prove that f(z) is holomorphic on T_Γ.